UMPSA student aspires to make university pioneer user-friendly and inclusive indoor navigation system - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 16 October 2025 – Realising the challenges faced by students and visitors in locating lecture rooms and laboratories at the Faculty of Computing (FK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), FK student, Ahmad Haziq Mohamad, 21, introduced an innovation named UMPSA Smart Navi: Real-Time Digital Navigation System for Campus Wayfinding.